Pengaruh Tingkat Pendidikan Orang Tua Terhadap Orientasi Pola Asuh Anak Usia Dini - Mohzana Mohzana; Hary Murcahyanto; Muh Fahrurrozi (Journal of Elementary School (JOES), 2024)
This study aimed to explain and prove the causal relationship between parents' education level and parenting. This research was conducted in one of the PAUD schools in East Lombok Regency. The research method used was quantitative with the type of ex post facto correlational research. The population used was the parents of 20 students who were taken using a non-probability sampling technique. Data collection techniques used observation, documentation, and closed questionnaires. Data processing was carried out using statistical analyses such as validity, reliability, and prerequisite analysis tests with t-tests to test hypotheses. The resulting data is then entered into the preparation table to find the value of X, Y, X2, Y2, and XY. The results of this study are, the higher the level of education of parents, the better their understanding of providing parenting to children, while the lower the level of education of parents, the lower the parents' understanding of parenting. Democratic parenting is the most common parenting pattern applied in PAUD compared to authoritarian and permissive parenting and is considered the best parenting pattern because it can shape children into individuals who trust others, take responsibility for their actions, are not hypocritical, and are honest. It is concluded that parents' education level significantly influences early childhood parenting in PAUD. Keywords: early childhood, parenting orientation, education level